Evaluating the spatiotemporal patterns of GPP and tree growth for their response to CO2 fertilization effects in mid-latitude forests of China - Bin Wang; Xiangqi Kong; Shaojie Bian; Ying Quan; Zechuan Wu; Jianyang Liu; Mingze Li (Geo-spatial Information Science)
The investigation of the spatiotemporal variation trend of the atmospheric CO2 fertilization effect ([Formula: see text]) has emerged as a prominent topic of interest on a global scale in recent times. Nevertheless, the spatiotemporal patterns of [Formula: see text] remain unclear. Herein, we selected the mid-latitude forests of China as the designated study region. Accordingly, remote sensing Gross Primary Productivity (GPP) products were used along with model-based GPP simulation results and tree-ring data in this study. This was combined with the random forest algorithm and a moving window approach to assess the spatiotemporal patterns of vegetation productivity and tree growth responses to atmospheric CO2 variations between 1982 and 2015. Our findings suggest that from 1982 to 2015, the estimated [Formula: see text] derived from the two remote sensing GPP products demonstrated a declining trend. In particular, the EC-LUE GPP exhibited a decrease rate of −0.46%.100 ppm−1yr−1, while the NIRv GPP showed a decrease rate of −0.04%.100ppm−1yr−1. Similarly, the findings from the estimation based on models also indicated a decline in [Formula: see text], with an average decrease rate of −0.08%.100 ppm−1yr−1 across a total of 18 models. Based on the analysis of tree rings from 16 sites, it was observed that the radial growth response of vegetation to atmospheric CO2 exhibited a decline with an average decrease rate of −0.81%.100 ppm−1yr−1. We speculated that the observed trend in β is primarily driven by LAI and forest age.